2011
DOI: 10.1007/s00122-011-1545-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a new stripe rust resistance gene Yr47 and its genetic association with the leaf rust resistance gene Lr52

Abstract: Two Iranian common wheat landraces AUS28183 and AUS28187 from the Watkins collection showed high levels of seedling resistance against Australian pathotypes of leaf rust and stripe rust pathogens. Chi-squared analyses of rust response segregation among F(3) populations derived from crosses of AUS28183 and AUS28187 with a susceptible genotype AUS27229 revealed monogenic inheritance of leaf rust and stripe rust resistance. As both genotypes produced similar leaf rust and stripe rust infection types, they were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 21 publications
5
35
0
Order By: Relevance
“…The Watkins collection is proven to host interesting alleles, particularly for disease resistance (Dyck 1994; Bansal et al 2011; Thompson and Seymour 2011), which are mainly Mendelian genes and comparatively easy to identify. In order to facilitate the use of the collection, particularly for more complicated phenotypic screens, a core set of 119 lines was defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Watkins collection is proven to host interesting alleles, particularly for disease resistance (Dyck 1994; Bansal et al 2011; Thompson and Seymour 2011), which are mainly Mendelian genes and comparatively easy to identify. In order to facilitate the use of the collection, particularly for more complicated phenotypic screens, a core set of 119 lines was defined.…”
Section: Discussionmentioning
confidence: 99%
“…The Watkins collection has been successfully used to find new alleles or genes for leaf rust resistance (Dyck 1994), stripe rust resistance (Bansal et al 2011), and root-lesion nematode resistance (Thompson and Seymour 2011). However, all of these are Mendelian traits, and the determination of the chromosomal locations for such traits is comparatively easy.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between QYrco.wpg-5B and YrExp1 is unknown and warrants further investigation. The relationship of QYrbr.wpg-5B with Yr47 has not been determined, as this gene has not been tested with any U.S. races [78]. QYrbr.wpg-5B was derived from Coda and both Madsen and Tres have the same haplotype, indicating both parents may carry this QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Yr47 (Bansal et al 2011) and Yr51 (Randhawa et al 2014) were previously identified from the Watkins collection, and Yr57 adds to the contribution of this collection in providing new genetic variation for stripe rust resistance. Six more genotypes are currently being investigated for potentially new sources of seedling resistance to stripe rust (Bariana and co-workers unpublished results).…”
Section: Test Of Allelismmentioning
confidence: 97%